A Nomogram Based on Laboratory Data, Inflammatory Bowel Disease Questionnaire and CT Enterography for Activity Evaluation in Crohn’s Disease - Zhang H; Shen Y; Cao B; Zheng X; Zhao D; Hu J; Wu X (Journal of Inflammation Research)
Han Zhang,1,* Yi Shen,1,* Bo Cao,2 Xiaomin Zheng,1 Dehan Zhao,3 Jing Hu,4 Xingwang Wu1 1Department of Radiology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People’s Republic of China; 2Department of Radiology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, 210011, People’s Republic of China; 3Department of Precision Machinery and Precision Instrumentation, University of Science and Technology of China, Hefei, Anhui, 230022, People’s Republic of China; 4Department of Gastroenterology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Hu, The First Affiliated Hospital of Anhui Medical University, Department of Gastroenterology, Hefei, Anhui, 230022, People’s Republic of China, Tel +86 139-5510-7753, Email hujing810@163.com Xingwang Wu, The First Affiliated Hospital of Anhui Medical University, Department of Radiology, Hefei, Anhui, 230022, People’s Republic of China, Tel +86 153-7533-0696, Email duobi2004@126.comBackground: Accurately assessing the activity of Crohn’s disease (CD) is crucial for determining prognosis and guiding treatment strategies for CD patients.Objective: This study aimed to develop and validate a nomogram for assessing CD activity.Methods: The semi-automatic segmentation method and PyRadiomics software were employed to segment and extract radiomics features from the spectral CT enterography images of lesions in 107 CD patients. The radiomic score (rad-score) was calculated using the radiomic signature formula. Multivariate logistic regression analysis identified the independent risk factors of erythrocyte sedimentation rate, fecal calprotectin, and Inflammatory Bowel Disease Questionnaire (IBDQ), and a nomogram was constructed in combination with rad-score. The nomogram underwent evaluation and testing in the training set (n = 84) and validation set (n = 23), respectively.Results: The discrimination performance of the combined (AUC 0.877) was marginally superior to that of IBDQ + clinical (AUC 0.854). However, there was no significant difference in AUC between the two models in the validation set (P = 0.206). IBDQ + clinical outperformed clinical (AUC 0.808), clinical outperformed IBDQ (AUC 0.746), and IBDQ outperformed radiomic signature (AUC 0.688). Significant differences in AUC were observed between the two models (radiomic signature vs clinical, P = 0.026; radiomic signature vs IBDQ + clinical, P = 0.011; radiomic signature vs combined, P = 0.008; in the validation set).Conclusion: The nomogram, combined with laboratory data, IBDQ and rad-score, presents an accurate and reliable method for assessing CD activity.Clinical Impact: The nomogram enhances the potential for personalized treatment plans and better disease management, making it a valuable tool for clinical practice.Keywords: Crohn’s disease, laboratory data, quality of life, nomogram, CT enterography